If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 6z = 7 + 5y Solving 6x + 6z = 7 + 5y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6z' to each side of the equation. 6x + 6z + -6z = 7 + 5y + -6z Combine like terms: 6z + -6z = 0 6x + 0 = 7 + 5y + -6z 6x = 7 + 5y + -6z Divide each side by '6'. x = 1.166666667 + 0.8333333333y + -1z Simplifying x = 1.166666667 + 0.8333333333y + -1z
| -20+18t=-(6t-4) | | 5x+7z=2+7y | | 5sinx+7cosx=2 | | V(x)=x(5-2x)(10-2x) | | 7sinx+7cosx^2=7 | | 2g+5=1g-4 | | a^2+b^2=40000 | | 2(x+5)(x-2)=x(x+5)+90 | | -6x^2-3x-3=0 | | 3x-8=2+4x-8 | | 7x-3(c+6)=14 | | 26x+4=18 | | 2x=80-2x | | 0.36/8 | | 10n^2-29n-44=0 | | 445-6x=0 | | -34z=14 | | -((2x)/(x-1)^3)=0 | | 4x^2-49x-900=0 | | 4x-9-6x=2(x+5)-3 | | 0.5x+0.3=.2 | | -5x-12y=15 | | 6*6/2(3)=4 | | -0.5(x-2)=-x-2 | | 2(x-16)=0 | | -((20x)/sqrt(9-20x^2)=2 | | y/8-x/4=1 | | 13x-1=116 | | y=2x^2+(4)x-7 | | -((20x)/(9-20x^2)^(1/2))=2 | | 2x+(3x)=25 | | 4(2-6x)=6(2-4x) |